Investigation of the role of the jumping-to-conclusions bias for short-term functional outcome in schizophrenia - Andreou, Christina; Treszl, András; Roesch-Ely, Daniela; Köther, Ulf; Veckenstedt, Ruth; Moritz, Steffen (Psychiatry research, 2014)
Symptom severity and neuropsychological deficits negatively influence functional outcomes in patients with schizophrenia. Recent research implicates specific types of biased thinking styles (e.g. jumping-to-conclusions) in the pathogenesis of schizophrenia. This is the first study to test the impact of jumping-to-conclusions on functional outcome in schizophrenia. The aim of the study was to investigate the association of psychopathology, neuropsychology and JTC with subjective quality of life, vocational outcome and housing status in schizophrenia. Analyses were carried out both cross-sectionally at baseline, and longitudinally over the course of symptomatic improvement in the immediate aftermath of a psychotic exacerbation. Seventy-nine patients with schizophrenia were included in the study. Data concerning the variables of interest were collected at baseline, after one month, and after six months. Positive symptomatology was the most significant predictor of subjective and vocational outcome and changes across time. Verbal memory deficits were associated with functional status cross-sectionally, whereas general cognitive capacity significantly predicted functional changes over time. Improvement of the jumping-to-conclusions bias positively affected vocational outcome. Though limited, the observed effect of this bias on real-world functioning highlights the possible usefulness of interventions aimed at improving (meta)cognitive deficits in schizophrenia.